The implementation of the Final Peace Agreement with the FARC: a prospective analysis from public policies (2018)
This article seeks to recover the expression and meaning of the term "implementation" for that which refers to the execution of the purposes established in the Peace Agreement, from the view point of public policy literature. The article aims to document and analyze the organizational assumptions of the 310-page text, showing its main trends, especially the high number of organizations involved and the high sectorial complexity. In methodological terms, this study will be done under the lines indicated by the third generation of implementation studies, which requires defining a hypothesis and intervening variables to analyze implementation. To this end, the study bases its conceptualization in the seminal study by Pressman and Wildavsky (1973), which indicates that the risk of failure in implementation increases with the greater number of steps, decisions and intervening actors. Given this, the article first undertakes an inventory of the organizations involved in the agreement; secondly, it classifies these organizations in terms of their decision-making complexity; and thirdly, and finally, it explores the sectors with the most complex implementation designs. The article concludes that in organizational terms, the Colombian accord with FARC is a highly complex and maximalist agreement.